Prospects and Problems of Expanding Trade with Japan: A Survey of Philippine Exporters - Palanca-Tan, Rosalina (Archīum Ateneo, 2004)
The paper looks at firm-level factors that affect Philippine exports to Japan with the main objective of recommending provisions for the proposed Japan-Philippines Economic Partnership Agreement (JPEPA) that will enable existing and prospective Philippine exporters to fully exploit the potential of the Japanese market. To this end, the study identifies Philippine products with export prospects in Japan and conducts a SWOT (Strengths, Weaknesses, Opportunities, Threats) Analysis of these production sectors. The inability of the Philippine agricultural, processed food and consumer manufactures to successfully tap into the growing import markets of Japan can be traced largely to low quality and price competitiveness arising from insufficient technical know-how, lack of economies of scale and credit facilities for small and medium enterprises (SMEs) that comprise roughly 90% of the exporters, certain distortionary government policies, and insufficient infrastructure and government support. Apart from these domestic factors, there is severe competition from China, Thailand, Indonesia and Vietnam, and there remains the protection and regulation of the Japanese markets. The complete opening of Japan’s agricultural and processed food sectors to the Philippines, import promotion programs particularly for Philippine made products, and SME-focused efficiency enhancement training programs and capital accumulation loan programs may, thus, be necessary if Japan is to assist the Philippines expand its exports. Further, the benefits that the Philippines can reap from the optimal position of its electronics and automotive parts exports in Japan may be enhanced if support industries develop in the Philippines which requires among other things Japanese assistance for human resources development programs.